Prescriptions for Rural Mathematics Instruction: Analysis of the Rhetorical Literature - Craig B. Howley; Aimee A. Howley; Donna S. Huber (Journal of Research in Rural Education, 2005)
Very little empirical research has examined mathematics education in rural schools and communities. A modest nonresearch literature does exist, however, and this study analyzed this literature. We found 3 themes describing the prescriptions given to rural educators: (a) mathematics education in rural schools needs to be fixed; (b) good things happen in some rural schools; and (c) fixing mathematics instruction requires certain practices. These practices include providing challenging curriculum, undertaking professional development efforts, making use of distance-learning options, and engaging local support. In general, the prescriptions given in this literature loosely reflect conventional wisdom in their support of the National Council of Teachers of Mathematics standards and the exigencies of the various state-level accountability schemes. The nonresearch literature only rarely tied its prescriptions to any relevant empirical research (either general or rurally focused). In an extended discussion, we critique the influence of deficiency theory on the themes evident in this literature. We conclude that a strong need for a rurally focused empirical work exists and recommend that it be informed by a critical reading of mathematics education practice in rural places. Issues surrounding the rural lifeworld, especially in the context of globalization, would have much to contribute toward the development of such a literature.